(untitled) (Global Journal of Human-Social Science, 2012)
Introduction -Children in slums have a poor quality of life. The lack of basic services affects them the most. Children are most disadvantaged in slums. Girls have to look after younger siblings when both parents go to work. Combined with a traditional bias against educating girls they are often not sent to school or drop out at an early stage. Girls do not have the exposure to everyday city life situations, which men, women and young men have. As a result they are often anxiety prone and stressed. The unhealthy and polluted environment, lack of immunization, malnutrition and absence of educational exposure affects children in slums. Sadly, their physical, emotional and intellectual growth is stunted from a very early age.